2021
DOI: 10.1080/00325481.2021.1974212
|View full text |Cite
|
Sign up to set email alerts
|

Nuts and bolts of COVID-19 associated coagulopathy: the essentials for management and treatment

Abstract: Introduction COVID-19-associated coagulopathy (CAC) is a well-recognized hematologic complication among patients with severe COVID-19 disease, where macro- and micro-thrombosis can lead to multiorgan injury and failure. Major societal guidelines that have published on the management of CAC are based on consensus of expert opinion, with the current evidence available. As a result of limited studies, there are many clinical scenarios that are yet to be addressed, with expert opinion varying on a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…In addition, a meta-analysis in 2021 suggested that almost 3% of COVID-19 patients may develop DIC and this condition may increase the likelihood of mortality by more than 2.4 times [ 42 ]. Therefore, monitoring and diagnosis of CAC is a major challenge in the management of COVID-19 patients [ 43 ]. Reports have revealed that COVID-19 patients, particularly with ARDS, may represent hypercoagulability state, i.e., higher levels of D-dimer, mild prolongation of PT and PTT, and thrombocytopenia [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis in 2021 suggested that almost 3% of COVID-19 patients may develop DIC and this condition may increase the likelihood of mortality by more than 2.4 times [ 42 ]. Therefore, monitoring and diagnosis of CAC is a major challenge in the management of COVID-19 patients [ 43 ]. Reports have revealed that COVID-19 patients, particularly with ARDS, may represent hypercoagulability state, i.e., higher levels of D-dimer, mild prolongation of PT and PTT, and thrombocytopenia [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%